Knowledge of COVID-19 and Its Influence on Mindfulness, Cognitive Emotion Regulation and Psychological Flexibility in the Indian Community - Dubey, Neha; Podder, Priyanka; Pandey, Dinkar (Frontiers in Psychology, 2020)
ABSTRACT The current global pandemic caused by COVID-19 has brought about an immense effect on the mental health of the general public. Considering the escalation in number of cases, mankind is facing a myriad of psychological problems, ranging from those related to taking precautions and maintaining safety to the ones caused by separation and bereavement. The current study aims to explore whether there is a significant difference between individuals with excellent, good, fair and vague knowledge of COVID-19 with respect to depression, anxiety, stress, level of mindfulness, specific cognitive emotion regulation strategies and psychological flexibility; to find out whether there is any significant relationship among these variables; and to determine whether knowledge of COVID-19, level of mindfulness, specific cognitive emotion regulation strategies and psychological flexibility are significant predictors of depression, anxiety and stress in the sample of the current study. The sample consisted of 402 individuals selected from the community following the research criteria. Data was collected using digital consent form, information schedule and questionnaires, from 3rd May to 13th May, 2020. The questionnaires consisted of a semi-structured interview schedule to assess knowledge of COVID-19, Depression, Anxiety and Stress Scale - 21, Five Facet Mindfulness Questionnaire-Short Form, Cognitive Emotion Regulation Questionnaire-Short version and Acceptance and Action Questionnaire-II. The data was statistically analyzed using analysis of variance test, correlational analysis and linear regression. The findings show that significant differences were present among individuals having varying degrees of knowledge of COVID-19 with respect to anxiety, level of mindfulness and psychological flexibility. Significant relationships were found to be present among the variables of the present study, having differing trends brought forward by the COVID-19 crisis. Certain socio-demographic characteristics and study variables were found to significantly predict the existing levels of depression, anxiety and stress in the current sample. The study suggests the necessity to formulate and implement appropriate mindfulness-based therapeutic interventions to address the mental health concerns arising as a result of the pandemic.